Clinical audit of foot problems in patients with rheumatoid arthritis treated at Counties Manukau District Health Board, Auckland, New Zealand - Rome, K; Gow, PJ; Dalbeth, N; Chapman, JM (BioMed Central Ltd, 2009)
Background At diagnosis, 16% of rheumatoid arthritis (RA) patients may have foot joint involvement, increasing to 90% as disease duration increases. This can lead to joint instability, difficulties in walking and limitation in functional ability that restricts activities of daily living. The podiatrist plays an important role in the multidisciplinary team approach to the management of foot problems. The aim of this study was to undertake a clinical audit of foot problems in patients with RA treated at Counties Manukau District Health Board. Methods Patients with RA were identified through rheumatological clinics run within CMDHB. 100 patients were eligible for inclusion. Specific foot outcome tools were used to evaluate pain, disability and function. Observation on foot lesions were noted and previous history of foot assessment, footwear/insoles and foot surgery were evaluated. Results The median age of the cohort was 60 (IQR: 51–64) years old with median disease duration of 15 (IQR: 7.3–25) years. Over 85% presented with foot lesions that included corns and callus over the forefoot region and lesser toe deformities. Moderate to high disability was noted. High levels of forefoot structural damage were observed. 76% had not seen a podiatrist and 77% reported no previous formal foot assessment. 40% had been seen at the orthotic centre for specialised footwear and insoles. 27% of RA patients reported previous foot surgery. A large proportion of patients wore inappropriate footwear. Conclusion This clinical audit suggests that the majority of RA patients suffer from foot problems. Future recommendations include the provision of a podiatrist within the current CMDHB multidisciplinary rheumatology team to ensure better services for RA patients with foot problems.